2012
DOI: 10.1093/occmed/kqs021
|View full text |Cite
|
Sign up to set email alerts
|

The HSE indicator tool, psychological distress and work ability

Abstract: The study presents new evidence for the validity of the HSE indicator tool to estimate the risk of work-related stress and suggests that most but not all the effects of psychosocial conditions on work ability might be mediated by the level of psychological distress induced by these conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
2
7

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 20 publications
4
33
2
7
Order By: Relevance
“…The results that PD was associated with an increased probability of poor work ability conforms to the findings of several previous studies. A cross‐sectional study reported that PD, measured by GHQ‐12, could explain 47% of the variance in the WAI scores [Guidi et al, ]. Another cross‐sectional study found that perceived health status (i.e., mental health, vitality, role limitations due to emotional or physical problems, pain, general health perceptions and physical and social functioning) rather than working conditions, could explain a large part of the decreased work ability among workers with a chronic health condition [Koolhaas et al, ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results that PD was associated with an increased probability of poor work ability conforms to the findings of several previous studies. A cross‐sectional study reported that PD, measured by GHQ‐12, could explain 47% of the variance in the WAI scores [Guidi et al, ]. Another cross‐sectional study found that perceived health status (i.e., mental health, vitality, role limitations due to emotional or physical problems, pain, general health perceptions and physical and social functioning) rather than working conditions, could explain a large part of the decreased work ability among workers with a chronic health condition [Koolhaas et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Since workers with PD are at an increased risk for poor work functioning [Guidi et al, ], it is important to learn if their work ability could be improved by favorable job characteristics. Such knowledge is of value in order to decide whether and if so, what preventive measures to be taken.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that the HSE indicator is correlated with mental wellbeing as measured with the GHQ-12 (Guidi et al 2012) and with general (Kerr et al 2009) and job-related (Main et al 2005) anxiety and depression. The HSE standards are also a set of national standards which act as a baseline against which measurements can be assessed (Cousins et al 2004).…”
Section:  Limitations Of the Evidence Base In Generalmentioning
confidence: 99%
“…There is also ample evidence that high-risk conditions for work-related stress have a detrimental impact on workers’ health and safety, with a clear relation in particular with cardiovascular diseases [4], mental [5] and musculoskeletal disorders [6] and workers’ psychosocial well-being [7,8]. Work-related stress can also affect an organization’s productivity and competitiveness, with further impact on social and economic costs [1,9].…”
Section: Introductionmentioning
confidence: 99%